Influence of volatile fatty acid concentration on biogas production in synthropic anaerobic digestion - Sinaga, Nazar; Mel, Maizirwan; Pakpahan, Rezeki; Che Sidik, Nor Azwadi (Akademia Baru, 2017)
Biogas is one type of renewable energy that can be produced from substrates in the form of industrial waste. Biogas formation is a complex series of biochemical processes and involves many types of anaerobic micro-organisms. In an anaerobic digester, synthropic reactions are considered to be the process steps that limit the formation of this biogas. This study aims to study the effect of volatile fatty acid substrate concentration (VFA) on the biogas production rate in a digester tank equipped with Rushton Impeller 6 bladed type mixer, which is rotated at a constant speed of 100 rpm. The simulations were performed in 3 dimensions under transient conditions using computational fluid dynamic (CFD) methods that are tied to the equilibrium equations of the synthropic reaction population (acetogenesis and methanogenesis) in the stirred reactor. This simulation uses a 3-phase Eulerian model and a k-epsilon RNG turbulence model to solve the momentum equation, species transport and population balance equation. The preferred solution method is PC-SIMPLE with First Order Upwind discretization. In this study 8 variations of substrate concentration were simulated. The validation results of the previous research showed very close results, with the difference is less than 1%. Hence, the VFA degradation process occurs efficiently and the VFA concentration profile in the 3-phase system is a heterogeneous flow pattern, so it is concluded that the calculation model used can be used to predict the biogas production rate quite well. Based on the simulation results of 8 types of VFA substrate concentrations observed after 70 seconds, it was found that the production and concentration of methane in biogas varied between 17.62% (variation-6) to 22.96% (variation-5). The biogas production varies between 0.61 g/l (reference model) to 0.95 g/l (variation-3). With this investigation, it can be done by simulation to get optimal mixer design, according to the type of substrate used and operating conditions of the digester.